Ghrelin levels are suppressed and show a blunted response to oral glucose in women with polycystic ovary syndrome. - Barber, T; Casanueva, F; Karpe, F; Lage, M; Franks, S; McCarthy, M; Wass, J (2008)
OBJECTIVE: Abnormal ghrelin regulation may influence the development of obesity-associated conditions including polycystic ovary syndrome (PCOS). Our aim was to compare ghrelin regulation between PCOS cases and controls. DESIGN: We compared serum ghrelin (total) levels, fasting and 30-min post-oral (75 g) glucose load, between 50 PCOS cases and 28 female controls, including 22 body mass index (BMI)/fat mass-matched pairs. All subjects were of UK British/Irish origin. METHODS: Measurements included serum ghrelin (RIA technique (LINCO Research, St Charles MO, USA)), fat mass, serum testosterone, fasting serum insulin and plasma glucose levels. Insulin sensitivity was calculated as the homeostasis model assessment of insulin resistance (HOMA2 IR). RESULTS: Fasting serum ghrelin levels were significantly lower in PCOS cases versus BMI/fat mass-matched controls (geometric mean (s.d. range), 1104 pg/ml (764-1595) vs 1756 pg/ml (1314-2347) respectively; P=2.3 x 10(-4)). Ghrelin suppression following oral glucose load was significantly blunted in PCOS cases versus BMI/fat mass-matched controls (geometric mean ghrelin suppression (s.d. range), 160 pg/ml (88-289) vs 424 pg/ml (220-818) respectively; P=2.0 x 10(-4)). Whole-group comparisons (50 PCOS cases versus 28 controls) adjusted for fat mass and age revealed similar results. In PCOS cases, there was a significant negative correlation between fasting serum ghrelin and HOMA2 IR (r(2)=-0.40, P=5.7 x 10(-3)). Following adjustment for HOMA2 IR, fat mass and age, comparisons between the whole groups of PCOS cases and controls revealed attenuated but significant differences in fasting serum ghrelin (P=1.3 x 10(-3)) and ghrelin suppression (P=1.8 x 10(-3)). CONCLUSIONS: In women with PCOS, serum ghrelin levels are suppressed, showing a negative relationship with HOMA2 IR and a blunted response to oral glucose.